Defining Paenibacillus azoreducens (P8) and Acetobacter pasteurianus (UMCC 2951) strains performances in producing acetic acid - Warawut Krusong; Salvatore La China; Ruttipron Pothimon; Maria Gullo (Frontiers in Microbiology, 2022)
P8 can be propagated in fermenting broths for boosting acetic acid production, under the selected conditions, and used in combination with acetic acid bacteria to produce biological acetic acid, as a non-food grade commodity.
Keywords: Microbial Metabolic Engineering and Bioproduction; Biofuel production and bioconversion; Chemical and Physical Properties in Aqueous Solutions